The effect of Covid-19 on the economy of Bangka-Belitung and the performance of MSME and its impact on competitive strategies in the new normal era - Reniati Reniati; Muhammad Faisal Akbar; Nur Ahmad Ricky Rudianto (Annals of Management and Organization Research, 2019)
Purpose: The economy in the MSME sector is experiencing a great crisis in the face of the Covid-19 pandemic. MSME actors must change strategies to adapt to the current pandemic conditions. The purpose of this study was to examine the effects of Covid 19 on the economy and performance of MSMEs as well as the strategies adopted by MSME players in Bangka Belitung Province. Research methodology: The data collection method employed probability sampling with google form media analyzed by using cross tabulation, trend analysis and simple mathematical modeling in projecting total economic losses to MSMEs that are active in the Bangka Belitung Island Province. Results: The results show that 84.7 percent of MSMEs experienced a negative impact due to the Covid 19 pandemic in the form of a decrease in sales turnover, reduced demand and hampered distribution of raw materials. However, 15.3 percent of MSMEs experienced a positive impact and survived in the Covid 19 pandemic conditions. Some of the strategies implemented by MSMEs to survive in the Covid 19 periods were replacing products sold with products for handling COVID 19 such as masks, hand sanitizers and others. MSME players also changed their sales strategy by selling online and maintaining customer databases. Limitation: Due to the Covid-19 condition, survey activities were carried out by using the Google Form online application. Contribution: MSMEs undertook a more aggressive marketing strategy to maintain turnover value in order to keep growing. Keywords: Covid-19, MSME, Turnover, Competitive strategy